Late Pleistocene Slip Rates on an Active Normal Fault in the Northwestern Ordos Block, China - Liu, Xingwang; Gao, Zemin; Shao, Yanxiu; Yao, Yunsheng (Frontiers in Earth Science, 2022)
The slip rates of normal faults on the northern margin of the Ordos Block are critical for understanding the deformation of the Ordos Block and adjacent areas. In this study, we obtain the late Pleistocene slip rate of an active normal fault, the Zhuozishan West Piedmont Fault (ZWPF), in the northwestern corner of the Ordos Block. Satellite imagery interpretation and field investigations suggest that the fault displaces late Pleistocene alluvial fans and forms west-facing fault scarps. To quantify the vertical slip rate of the ZWPF, we measured the displacements along the fault scarps using differential GPS and an unmanned aerial vehicle system and dated the displaced geomorphic surfaces using optically stimulated luminescence (OSL) dating methods. The vertical slip rate of the fault is constrained to 0.1 ± 0.02 mm/a, which suggests a horizontal extension rate of 0.05 mm/a for a dip of 65°. This rate is consistent with those on similar structures in the northwestern Ordos Block. Combining this result with published slip rates along other active faults, we infer that the NW-directed extension rate across the northwestern corner of the Ordos Block is ~0.6-1.3 mm/a. This rate is comparable with the geodetic strain rate. Given the extension rate, we believe that extensional deformation is mainly occurred on the western side of the basin.